Hábito de frutificação, crescimento e produção de pereiras tipo européia em função de diferentes porta-enxertos, na região Sul do Brasil. - Pasa, Mateus da Silveira (2011)
The pear crop is weak in Brazil, although there are regions suitable for cultivation, as the South Region. This mainly due to lack of studies on the most adapted cultivars, the best rootstock x scion, floral abortion and knowledge about bearing habit of the main cultivars. The objective of this study was to evaluate the bearing habit, growth, production and quality of pear of the cultivars Carrick, Packham's Triumph and William's grafted on different quince rootstocks and Pyrus calleryana. In the first part of the study it was evaluated the bearing habit, in which we assessed the following variables: percentage of vegetative spurs, reproductive spurs, vegetative brindles, reproductive brindles and borses and total number of flower buds. In this first part we obtained the following results: the bearing habit of cultivars (cvs) Carrick, Packham's and William's is influenced by different rootstocks; in all cultivars tested, regardless of the rootstock, in general, there was an inverse relationship between the percentage of vegetative spurs and reproductive spurs; the most significant influence of the rootstock is about reproductive spurs formation of the cultivars evaluated; cultural management in the orchards of cvs. Carrick, Packham's and William's, especially on the pruning operation should be oriented according the rootstock used. In the second part of the study it was evaluated production, growth and quality of fruit through the following variables: plant production (kg plant-1), productive efficiency (kg.m-3), total soluble solids (TSS), expressed in ºbrix, firmness (PF), expressed in kilograms; latter two variables were performed using non-destructive analysis trough NIR-Case (SACM); fruit mass (kg); fruit diameter (mm); trunk diameter (mm) and branch length (cm). According with the results obtained, the cvs. Carrick, Packham's and William's are more efficient when grafted onto the rootstock of quince 'Portugal' and 'MC'; 'Adam's', 'D'Angers' and 'Smyrna'; and 'Champion', respectively; the productive efficiency of cvs. Carrick, Packham's and William's, in general, is inversely proportional to the vigor induced by rootstocks; fruits of cvs. Carrick, Packham's and William's tend to accumulate a larger amount of soluble solids (TSS) when grafted on less vigorous rootstocks. .